“Throne of Claudius”: on Interpretation of Allegorical Relief from Cerveteri - Zashliapin, Boris D. (Actual Problems of Theory and History of Art, 2015)
In 1840 a marble slab with an image in relief was found at Cerveteri. From the very beginning it has attracted attention of many scholars. This was based on the peculiar interest of Europeans to Etruscan art in the mid-19th century. The connection between the characters of the relief follows from Latin inscriptions that denote exact Etruscan cities. Unfailing interest to the item is proved by the fascinating exhibition held in late 2013 — early 2014 in the Louvre-Lens, where the monument was among the key items. In this paper the author makes an attempt to consider the relief in quite a different way, not confined with the interpretations of the 19th century, some arguments of which are rethought. It is obviously possible that the scene on relief is closely connected with the understanding of afterlife and can illustrate the idea of ever-living Roman emperor and his divine power as referred to by different nations of the Empire.
Keywords: “throne of Claudius”; Cerveteri; Caere; Vulci; Tarquinii; Vetulonia; Etruscan League; Dodecapolis; Etruscans; Gregorian Profane Museum